COMPARATIVE ANALYSIS OF STEEL REINFORCED AND BAMBOO REINFORCED BEAMS - Abdourahim Jallow; Sri Murni Dewi; Ari Wibowo (Rekayasa Sipil, 2019)
This research will seek to compare bamboo reinforced concrete beams and steel reinforced concrete beams experimentally. Special emphasis will be laid on how both sets of beams respond to nominal moments. The main aim is to find out the applicability of bamboo reinforced concrete beams against steel reinforced concrete beams in developing countries wherein bamboo is easily available as compared to steel reinforcement bars. The behaviors in terms of crack patterns will be also discussed including their stress and strain behaviors as well under the same kind of loading and with the same loads applied.Two (2) sets of beams were designed to investigate three (3) parameters namely; compressive strength on concrete, longitudinal reinforcement and transverse reinforcement. All beam cross-sections were maintained throughout the experiment as well as cross-section areas of rebars in each case. The shapes of the rebars were different; round in the case of steel and rectangular in bamboo. All bamboo rebars were treated with Sikadur to improve their bond strengths.The steel reinforced beams were reinforced with 2f10mm for compression bar and 3f10mm and 6f10mmfor tension bars, which correspond to longitudinal reinforcement ratio of 0.42%, 0.63% and 1.26% respectively. Whereas, the bamboo reinforced bars(rebars) used 2 bars 8x8 mm (for compression bar) and two cases of 3 bars and 6 bars of 8×8 mm (for tension bars) corresponding to longitudinal reinforcement ratio of 0.34%, 0.51% and 1.02% respectively.The spacing of the stirrups (6mm steel bars) were 150mm and 300mm for each case. The beams were also investigated for the effect of strengths of concrete of 20MPa and 30MPa.